1992
DOI: 10.1159/000247422
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome and Systemic Sclerosis

Abstract: Carpal tunnel syndrome (CTS) was observed in 4 cases of a consecutive series of 16 patients admitted for the initial diagnosis or follow-up of systemic scleroderma from 1986 to 1990. We also observed one case of ulnar nerve compression. Neurological involvement was confirmed by electromyogram, and motor and sensory nerve conduction studies. The neurological signs appeared at the beginning of the disease in two cases and preceded the discovery of scleroderma in two. CTS is not rare in scleroderma and must be ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
1
9
1
Order By: Relevance
“…Among the participants in this study, the most common type of MNW was asymptomatic, which was similar to the previous studies [ 8 , 10 ]. Although most of the MNW cases were subclinical, which did not directly affect the routine activity of daily living in SSc patients, a manifestation sign of increased vulnerability to the expression of underlying diffuse damage to the peripheral nervous system was hypothesized.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the participants in this study, the most common type of MNW was asymptomatic, which was similar to the previous studies [ 8 , 10 ]. Although most of the MNW cases were subclinical, which did not directly affect the routine activity of daily living in SSc patients, a manifestation sign of increased vulnerability to the expression of underlying diffuse damage to the peripheral nervous system was hypothesized.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that MNW in SSc patients involves directly increased stiffness of the median nerve [ 7 ]. Therefore, the most common peripheral neuropathy in SSc patients is MNW, which occurs in about 3.2–44% [ 8 – 13 ]. The prevalence of MNW in such patients was higher than in the general population, which was found to be about 0.9–10% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 Trigeminal sensory neuropathy is the most frequent manifestation and occurs in 5-9% of patients with scleroderma. 2,11 Although neurologic complications occur in 0.8 -5.6% of patients in prospective studies, 8,21 generalized peripheral neuropathy was not observed in a series of 150 and 727 patients. 9,21 Of the 125 patients prospectively followed by Lee et al, only one had peripheral neuropathy and another mononeuritis multiplex.…”
Section: Discussionmentioning
confidence: 97%
“…However, skin biopsy evaluation was not performed in this study for the assessment of small fiber polyneuropathy. Following previously published recommendations for research in polyneuropathy, we required both clinical and NCS criteria for polyneuropathy to be fulfilled to make a diagnosis of definite large fiber symmetrical polyneuropathy 10 . Similarly, the correlation of clinical symptoms and NCS‐defined focal neuropathy was required before a diagnosis of definite focal neuropathy was made.…”
Section: Methodsmentioning
confidence: 99%
“…Second, direct nerve compression damage by calcinosis or edema in the early phase of disease and fibrosis in the advanced stage of disease may occur 6 . This can also contribute to focal entrapment neuropathies seen in SSc, commonly carpal tunnel syndrome 8‐10 . Third, the presence of anti‐neuronal antibodies linked to SSc could suggest an immune‐mediated mechanism directed toward the peripheral nerve 1 …”
Section: Introductionmentioning
confidence: 99%